Class and campus life : managing and experiencing inequality at an elite college - Lee, Elizabeth M., 1974- (ILR Press, an imprint of Cornell University Press, 2016)
In 2015, the New York Times reported, "The bright children of janitors and nail salon workers, bus drivers and fast-food cooks may not have grown up with the edifying vacations, museum excursions, daily doses of NPR and prep schools that groom Ivy applicants, but they are coveted candidates for elite campuses." What happens to academically talented but economically challenged "first-gen" students when they arrive on campus? Class markers aren't always visible from a distance, but socioeconomic differences permeate campus life--and the inner experiences of students--in real and sometimes unexpected ways. In Class and Campus Life, Elizabeth M. Lee shows how class differences are enacted and negotiated by students, faculty, and administrators at an elite liberal arts college for women located in the Northeast